Where Is the Way to the Dwelling of Light? : Studies in Genesis, Job and Linguistics in Honor of Ellen van Wolde - Van Loon, Hanneke; Van Hecke, Pierre (Biblical Interpretation Series, 2023)
Nineteen friends and colleagues present this Festschrift to Ellen van Wolde, honouring her life-long contribution to the field of Biblical studies. The contributions focus on the major topics that define her research: the books of Genesis and of Job, and study of the Hebrew language. Profoundly inspired by the lasting legacy of the jubilarian, the articles present innovative and thought-provoking developments in the linguistic study of the Hebrew Bible, with a particular attention to cognitive linguistics, and in the research - literary as well as linguistic - of two of its most fascinating books.